International experimental calligraphy - Qiang, Zhang; Jiarui, Han (Journal of visual art practice, 2023)
A visual presentation of Zhang Qiang's experimental calligraphy is set alongside a reading of the notion of 'International Experimental Calligraphy'. This term serves a dual purpose. Historically, it provides a framework to understand and acknowledge calligraphy from ancient times and unconventional writing practices within the context of Chinese calligraphy. It also serves to validate Western abstract expressionism as an experience aligned with calligraphy, so enriching a genealogical account of 'visual history'. In doing so, the poet and calligrapher, Su Shi, is a representative figure. His early thinking offers an important reminder that for Chinese calligraphy to be recognized as modern and contemporary, it needs to move beyond the confines of merely an intangible cultural heritage, and rather be understood an integrated aspect of an international, genealogical visual history.